Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]8^{3x - 1} = 2^8 ; 8 = 2^3 \\
(2^3)^{3x-1} = 2^8 \\
2^{9x-3} = 2^8 \\
9x-3=8 \\
9x=11 \\
x= \frac{11}{9} [/tex]
[tex]8^{(3x-1)}=2^8 \\\\ 2^{3(3x-1)}=2^8 \\\\ 3(3x-1)=8 \\\\ 9x-3=8 \\\\ 9x=8+3 \\\\ 9x=11 \\\\ \boxed{x=\frac{11}{9}}[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.